Stimuli-responsive, dual-function prodrug encapsulated in hyaluronic acid micelles to overcome doxorubicin resistance. (1st March 2022) - Qiu, Lipeng; Xu, Jiamin; Ahmed, Kamel S.; Zhu, Mengqin; Zhang, Yan; Long, Miaomiao; Chen, Weijun; Fang, Wenjie; Zhang, Huijie; Chen, Jinghua
Abstract: Multidrug resistance (MDR) is the main challenge faced by cancer chemotherapy. Drug-conjugate offers a promising strategy for breast cancer therapy. In this regard, we developed a DNVM multifunctional drug delivery system by crosslinking doxorubicin (DOX) and vitamin E succinate (VES) with a pH-sensitive hydrazone bond and then encapsulated the DOX-NN-VES prodrug into pH-sensitive hyaluronic acid-2-(octadecyloxy)-1, 3-dioxan-5-amine (HOD) micelles. DOX resistant MCF-7/ADR cell were adopted as a model to study the capability and mechanism of MDR reversal. DNVM exhibited much higher cytotoxicity and cell uptake efficiency compared with that of acid-insensitive DOX-VES loaded HOD micelles (DVSM) and DOX loaded HOD micelles (DOXM), indicating the better capacity of DNVM for the reversal of MDR. Moreover, DNVM prevented drug efflux more effectively, inhibited the expression of P-gp, induced excessive production of reactive oxygen species and affected the expression of apoptosis-related proteins. In vivo experiments showed that DNVM significantly inhibited the tumor growth with no obvious changes in the body weight of MCF-7/ADR cells-bearing nude mice. The results suggested that the "double gain" DNVM can synergistically enhance the efficacy of chemotherapeutics for DOX resistant tumor cells and has the potential to overcome tumor MDR. Statement of Significance: A dual-functional pH-sensitive doxorubicin - vitamin E succinate prodrug was developed and loaded into tumor microenvironment-sensitive hyaluronic acid-2-(octadecyloxy)-1, 3-dioxan-5-amine micelle system (DNVM) for sequencing stimuli-release and overcoming doxorubicin resistance. The "double gain" DNVM can synergistically enhance the efficacy of chemotherapeutics for doxorubicin resistant tumor cells and has the potential to overcome tumor multiple drug resistance. Graphical abstract: Image, graphical abstract